2008
DOI: 10.1684/agr.2008.0232
|View full text |Cite
|
Sign up to set email alerts
|

Prévention des invasions de criquets pèlerins : analyse socio-technique d’un dispositif de gestion du risque

Abstract: De par leur nature et leurs conséquences, les invasions de criquet pèlerin sont des phénomènes incertains, dynamiques et complexes auxquels des acteurs variés s'attachent à faire face. Les gestionnaires des invasions acridiennes établissent et « appareillent » des stratégies de surveillance et de lutte dont les résultats sont souvent difficiles à apprécier du fait de l'existence de situations de crise suivies de longs moments de rémission pendant lesquels les efforts de veille et de lutte peuvent parfois sembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The other results also show that the speed of the funding bodies' reaction to dealing with a locust crisis is proportional to the invasion that arises. This tallies well with some events described by the Food and Agriculture Organization of the United Nations (FAO) services that face lengthy administrative delays in releasing funds after the early warnings they issue . This also indicates that funders should rather keep their budget renewal threshold as low as possible if they are aware that a risk oversight will happen anyway.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The other results also show that the speed of the funding bodies' reaction to dealing with a locust crisis is proportional to the invasion that arises. This tallies well with some events described by the Food and Agriculture Organization of the United Nations (FAO) services that face lengthy administrative delays in releasing funds after the early warnings they issue . This also indicates that funders should rather keep their budget renewal threshold as low as possible if they are aware that a risk oversight will happen anyway.…”
Section: Discussionsupporting
confidence: 76%
“…who obtained similar results on the need to allocate a minimum effort to passive surveillance of invasive species. But unfortunately in current systems, the less attention the locusts receive, the more the funding decreases . Such a model could be used to convince donors – at international but also at national level − to provide greater and faster support in the event of a crisis but also over the long term.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, Gay et al 28 showed that the speed of the funding body's reaction to dealing with a locust crisis is proportional to the invasion that arises. The services of the Food and Agriculture Organization of the United Nations (FAO) in charge of providing emergency assistance to countries facing locust invasions often come up against administrative delays in releasing funds, 10,33,34 and funders need to show greater reactivity in response to an alert. Third, Gay et al 28 showed that if the interest of funders in supporting preventive management did not decrease, even after a long period without invasions, invasions could be virtually non-existent.…”
Section: Introductionmentioning
confidence: 99%